Comparison of Narrow-Versus Broad-Spectrum Antibiotics in Elderly Patients With Acute Exacerbations of Chronic Obstructive Pulmonary Disease. (February 2022) - Joyner, Kayla R.; Walkerly, Autumn; Seidel, Kelsey; Walsh, Nicholas; Damshekan, Neda; Perry, Tyler; Soric, Mate M.
Background: Little evidence is available regarding the choice of empiric antibiotic therapy in elderly patients with acute exacerbations of chronic obstructive pulmonary disease (AECOPD). The primary objective of this study is to compare the outcomes of elderly patients receiving broad- versus narrow-spectrum antibiotics during hospitalization for AECOPD. Design: A multicenter, retrospective, cohort analysis was performed. Inpatients 65 years and older with a primary discharge diagnosis of AECOPD who received ≥48 hours of antibiotic therapy were included in the study population. Patients were compared based on the spectrum of their antibiotic therapy. Narrow-spectrum antibiotics included: azithromycin, doxycycline, sulfamethoxazole/trimethoprim, or aminopenicillin. The primary outcome was a composite of mechanical ventilation 48 hours after admission, transfer to the intensive care unit 48 hours after admission, 30-day chronic obstructive pulmonary disease (COPD) readmission, and oxygen saturation less than 90% on room air or increased oxygen requirements from baseline 48 hours after admission. Results: Two hundred fifty-three patients were included in this analysis; 127 patients were included in the narrow-spectrum group, and 126 patients were included in the broad-spectrum group. Patient demographics and comorbid conditions were similarly distributed in each group. The incidence of the primary composite outcome occurred in 50 (39.3%) and 60 (47.6%) of patients in the narrow- and broad-spectrum groups, respectively ( P = .19). Conclusions and Relevance: No difference was found in the primary outcome in inpatients aged ≥65 years with AECOPD who received empiric broad-spectrum or narrow-spectrum antibiotics.